Immigration and public spending - René Böheim; Karin Mayr (Johannes Kepler University of Linz, Department of Economics, 2005)
We examine the effect of immigration on public spending from a theoretical (political economic) and an empirical perspective. We distinguish between public spending on private goods and on public goods. Our model implies that whether immigration increases or decreases public spending primarily depends on native's preferences for private versus public good spending. We empirically test our theoretical hypotheses, the `fiscal effect' and the `anti-social effect' of immigration using OECD panel data for 1990 - 2001. Estimating a system of simultaneous equations for total public spending and the share of spending on private goods, we find evidence for a negative effect of low-skilled immigration on public spending which is attributable to an anti-social effect. The effect of high-skilled immigration on public spending is positive, as suggested by a fiscal effect.
Keywords: F2; H4; H5; 330; immigration; cash transfers; public goods; Einwanderung; Öffentliche Ausgaben; Öffentliches Gut; Öffentlicher Transfer; Theorie; Makroökonomischer Einfluss